Analysis of the contract executed through public bidding LP-006-2021, in the municipality of Barrancas, department of La Guajira. (2022)
The purpose of this essay is to analyze the project that has been developed since the middle of the year 2021 and so far in 2022, in the municipality of Barrancas belonging to the department of La Guajira, which aims to make urban improvements and complementary works in the neighborhoods Los Olivos 1 and Pringamozal; The project was awarded during the month of September 2021 to the Barrancas urban park consortium, since it was the only bidder that submitted its proposal; the minutes containing the public works contract were signed by the parties in October of the same year with a stipulated execution time of seven (07) months. This analysis documents what has happened with the execution of said contract in each and every one of the different stages that have elapsed during this long year, especially in its contractual part, since the execution of the work began in January of this year and to date the contracted work has not been completed; therefore, we seek to focus attention on establishing the causes and reasons that have made possible the different contractual suspensions, thus causing delays in delivery times for more than four (04) months.